Investigation of the Annexin A5 M2 haplotype in 500 white European couples who have experienced recurrent spontaneous abortion. Issue 5 (November 2015) - Demetriou, Charalambos; Abu-amero, Sayeda; White, Shawnelle; Peskett, Emma; Markoff, Arseni; Stanier, Philip; Moore, Gudrun E.; Regan, Lesley
Abstract: Annexin A5 is a placental anti-coagulant protein that contains four nucleotide substitutions (M2 haplotype) in its promoter. This haplotype is a risk factor for recurrent spontaneous abortion (RSA). The influence of the M2 haplotype in the gestational timing of spontaneous abortions, paternal risk and relationships with known risk factors were investigated. European couples ( n = 500) who had experienced three or more consecutive spontaneous abortions, and two fertile control groups, were selected for this study. The allele frequency of M2 was significantly higher among patients who had experienced early RSA than among controls ( P = 0.002). No difference was found between controls and patients who had undergone late spontaneous abortions. No difference was found between patients who had experienced RSA who had a live birth or no live births, or between patients who were positive or negative for known risk factors. Male and female partners in each group had similar allele frequencies of M2. The M2 haplotype is a risk factor for early spontaneous abortions, before the 12th week of gestation, and confers about the same relative risk to carriers of both sexes. Having one or more M2 allele(s) in combination with other risk factors further increases the RSA risk.